Atypical Presentation of an Upper Lip Pleomorphic Adenoma: Case Report - Fotios Tzermpos; Chara Chatzichalepli; Alina Cocos; Manthos Kleftogiannis; Marissa Zarakas; Evanthia Chrysomali (University of Zagreb. School of Dental Medicine, 2014)
The pleomorphic adenoma (PA) or mixed tumour is the most common neoplasm of the salivary glands, usually presenting with a non-specific clinical manifestation and a diverse histopathological pattern. The region of the lips is the second most common site for minor gland neoplasms. The aim of this paper is to report the case of a 39 year old Caucasian woman presenting with a swelling on the right side of the upper lip combined with a history of trauma in the region of the upper right central incisor, eight years ago. The swelling was attributed to the periapical lesion of the upper right central incisor that was observed on the panoramic radiograph. Intraoperatively, the surgeon came upon a nodule of firm consistency in the mucolabial fold. The histopathologic diagnosis of this lesion was a benign mixed tumour of the salivary gland. This report discusses the deviation in frequency of mixed salivary gland tumour between upper and lower lip, the clinical differential diagnosis, the histopathological pattern and the appropriate treatment.